Approaching the transit time limit for high-precision spectroscopy on metastable CO around 6 μm. Issue 44 (30th October 2019) - D'Ambrosio, D.; Borri, S.; Verde, M.; Borgognoni, A.; Insero, G.; De Natale, P.; Santambrogio, G.
Abstract : We present a high-resolution spectroscopy experiment, based on a molecular beam setup, which pushes the measured line width close to the transit time limit, on the order of 100 kHz. Abstract : As molecular spectroscopy makes its comeback to the limelight of fundamental sciences, scientists need ever better coherent light sources and diagnostic methods. Of particular importance for molecular spectroscopy is the mid infrared spectral region, where strong and narrow ro-vibrational excitations have their fundamental transition frequencies. Unfortunately, much technology in some portions of this spectral region is still rather pioneering. Here we present a high-resolution spectroscopy experiment, based on a molecular beam setup, which pushes the measured linewidth close to the transit time limit, on the order of 100 kHz. Moreover, we discuss the issue of frequency-noise characterization and the linewidth measurement of the ultrastable infrared laser used in the experiment.